2011
DOI: 10.1103/physrevb.84.085131
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the energetics of charge and cation mixing in U1xCexO2

Abstract: The formalism of electronic density-functional-theory, with Hubbard-U corrections (DFT+U), is employed in a computational study of the energetics of fluorite-structured U1−xCexO2 mixtures. The computational approach makes use of a procedure which facilitates convergence of the calculations to multiple self-consistent DFT+U solutions for a given cation arrangement, corresponding to different charge states for the U and Ce ions in several prototypical cation arrangements. Results indicate a significant dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
0
26
1
Order By: Relevance
“…7,8,9 The number of vacancies required for xenon diffusion or the mechanism by which the xenonvacancy complex diffuse is not known experimentally. Because of the difficulty of measuring atomic scale properties, calculating these properties in UO 2 has been of interest using both Density Functional Theory (DFT) 7,10,11,12,13,14,15,16,17,18,19 as well as empirical potentials. 8,9,11,12,19,20,21,22,23 Several theoretical investigations of xenon in UO 2 have studied diffusion via a tetravacancy (TV, 2 V U + 2 V O ) mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,9 The number of vacancies required for xenon diffusion or the mechanism by which the xenonvacancy complex diffuse is not known experimentally. Because of the difficulty of measuring atomic scale properties, calculating these properties in UO 2 has been of interest using both Density Functional Theory (DFT) 7,10,11,12,13,14,15,16,17,18,19 as well as empirical potentials. 8,9,11,12,19,20,21,22,23 Several theoretical investigations of xenon in UO 2 have studied diffusion via a tetravacancy (TV, 2 V U + 2 V O ) mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to note that Hanken et al [15] ordering models equivalent to our pure layer models (namely their "CdI 2 " and "CuPt"…”
Section: Resultsmentioning
confidence: 84%
“…In any case, there are numerous theoretical studies of uranium-bearing complex oxides published in the literature, such as calculations of the electronic structure of Uranium-Americium complex oxides using DFT by Suzuki et al [14]. Another important study related to the work presented here involves molecular dynamics and DFT simulations of solid solutions of Ce 2 O 3 -UO 2 -UO 3 by Hanken et al [15,16], to establish the energetics of cation mixing.…”
Section: Introductionmentioning
confidence: 99%
“…In these calculations, a Hubbard-U correction was implemented within the formalism of Dudarev et al [39] to account for the self-interaction error for localized 5f electrons in uranium. The value of the parameter U eff = U-J in the DFT + U formalism was chosen to be 4.00 eV for this study; this value is similar to that found to give optimal results in comparisons with spectroscopic data for UO 2 by Dudarev et al (3.99 eV) [39], and was found to provide good agreement between calculated and measured oxidation enthalpies of UO 2 [40]. The PAW potentials used in this work are U, O, Y_sv and La in the VASP PBE library.…”
Section: First-principles Calculationsmentioning
confidence: 87%